If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(5x-90)=2x+30
We simplify the equation to the form, which is simple to understand
(5x-90)=2x+30
Remove unnecessary parentheses
5x-90=2x+30
We move all terms containing x to the left and all other terms to the right.
+5x-2x=+30+90
We simplify left and right side of the equation.
+3x=+120
We divide both sides of the equation by 3 to get x.
x=40
| C-6c=0 | | (11r+6)(5r-4)=0 | | Y=0.6(100)+b | | 6n^2/2 | | x+13=5x | | 5(x)=5(2x-3) | | R=b^2+1 | | (5x)2=15x-45 | | 3c-1=c | | 3x-5-x=2x-3 | | 3ysquared= | | 3(2x+1)-2(3-2)=13 | | 15x-45/2=5x | | 1/3x3/8 | | (7a)x(2b)=0 | | 15/105 | | 9z+4-5z-5= | | -6(r-7)=-54 | | 8+9a=7 | | 4x+3+2y=11 | | 7x-4.23=0.2+2.57 | | 7x-4.23=0.2 | | -8(n-2)-2=-21-3n | | 3x=2(7x-3) | | 80+5x=7x | | 4(5r-5)=-20-7r | | -5=7-2x | | (3x-1)(x+2)=-1 | | -x-3(-5x-8)=136 | | (12^5)/(9^2)*(4^4) | | 12^5/9^2*4^4 | | 0.3x-2(0.1x+0.4)= |